An Ethnographic Model of Stress and Stress Management in Two Canadian Inuit Communities. (May 2023) - Collings, Peter; Ready, Elspeth; Medina-Ramírez, Oswaldo M.
As part of the first stage of a community-based participatory research project with two communities in the Canadian Arctic—Kangiqsujuaq, Nunavik, and Ulukhaktok, Northwest Territories—we conducted 57 interviews eliciting residents' perceptions of pressing issues facing their communities, problems affecting health and wellbeing, and how researchers or other organized groups could help alleviate those problems. A recurrent theme that emerged during these interviews was having "no one to talk to." Here, we focus on understanding why communication was a central theme using a grounded-theory approach to develop a model of Inuit stress management. Inuit in both Kangiqsujuaq and Ulukhaktok codify stress as isumaaluttuq, or excess worry, which often manifests physically and leads to social withdrawal. Because stress is believed to accumulate in the body, managing it involves decisions about whether to "Get It Out" or "Keep It In." Keep It In is a potentially dangerous strategy because, if the problem does not resolve itself, accumulated stress may have harmful consequences. Inuit viewed talking to others as the most effective means to Get It Out, but respondents also identified numerous barriers to doing so. One important reason for this is that stress is transferable: Talking to others about a problem potentially increases the burden of stress on them. Consequently, Inuit may choose to Keep It In to avoid the potential negative consequences (for others or for oneself) of sharing bad thoughts. Based on this preliminary model, we consider questions for further inquiry and implications for community-based mental health programming in Inuit communities.